Climate Change Mitigation in India Today: A Review of Policy and Practice - Chandy, Smrithi K (South Asian Journal of Social Sciences and Humanities, 2020)
Climate change is one of the most widely debated issues, with far reaching adverse effects on agriculture, irrigation and water supply, health, energy, and so on. A universal understanding as well as coordinated action at the national level is required to address the impacts of climate change. There is a lot of contestation about the emission rate and carbon footprints of developed and developing countries. The major consensus lies in this area is that while developed countries contributed initially to the increased Green House Gases, while in the future, the blame is on developing nations. The adaptive capacity of the people in developing countries is generally low in developing countries, due to the inadequate attention given to this issue. However, the international policies adopted including the Kyoto protocol provisions and the efforts made by the UNFCCC are not enough to deal this global issue. Sustainable development strategies can be adopted by choosing energy-efficient ways, new and updated modifications in science and technology, renewable energy, advanced forestry methods, reforestation, and water saving strategies. Minimizing the vulnerability of the people belonging to different social and economic classes and ecosystems requires paramount consideration in the developing nations. Developing countries like India are facing the responsibility of mitigation and adaption strategies, affording the cost of such attempts and its inference for economic development.